KEDUDUKAN HUKUM DALAM PENGANGKATAN ANAK DAN PENGASUHAN FOSTER CARE: Studi Komparasi Hukum Indonesia Dan Amerika Serikat - Amanda Saskia Putri (2022)
The background of this research stems from the author's interest in Abraham Maslow's humanistic theory of social needs. One way to fulfill this social need is to have a family that literally consists of a husband, wife, and children. However, not all families have the same opportunity in terms of giving birth to children, so adoption is an option, and it turns out that there is also foster care. This study aims to the legal status of adopted children in Indonesia and the United States, while also discussing foster care in the two countries. This research is a type of normative juridical research that uses a statutory approach and a comparative approach. The data used is secondary data, which contains primary and secondary legal materials. Data was collected by means of library research. The results of the study indicate that the legal position of adopted children in Indonesia and the United States is influenced by the legal systems in force in the two countries. Regarding foster care, this type of care is familiar in America but still rarely discussed in Indonesia, and very little research has been found on foster care in Indonesia, so more massive socialization of this care is still needed. Keywords: legal status, adopted children, comparative law, foster care